The exiled fleet - Dewes, J. S. (Dewes, J. S. Divide series, 2021)
"The Sentinels narrowly escaped the collapsing edge of the Divide. They have mustered a few other surviving Sentinels, but with no engines, they have no way to leave the edge of the universe before they starve. Adequin Rake has gathered a team to find the materials they'll need to get everyone out. To do that they're going to need new allies and evade a ruthless enemy. Some of them will not survive"--